2010
DOI: 10.1007/s11250-010-9744-6
|View full text |Cite
|
Sign up to set email alerts
|

Ovicidal activity of seven Pochonia chlamydosporia fungal isolates on Ascaris suum eggs

Abstract: The ovicidal effect of the nematophagous fungus Pochonia chlamydosporia on eggs of Ascaris suum was tested under laboratory conditions. A. suum eggs were plated on 2% water-agar with seven fungal isolates (Isol. 5, Isol. 31, Isol. 1, VC1, Isol. 12, Isol. 22 and VC4) and control without fungus. After 5, 7, 10, 14, 15 and 21 days of incubation, approximately 100 eggs were removed from the plates and classified according to the following parameters: type 1, biochemical and physiological effect without morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
2
7
1
Order By: Relevance
“…Still, for chlamydospores production is important to stand out this structure viability for its use in biological control environment (Larsen 1999;Terrill et al 2004) The present study showed A. suum eggs destruction (type 3 effect) by P. chlamydosporia isolates (VC4 and VC1) after a long period of interaction. These results are in agreement with Ferreira et al (2011) and Araújo et al (2008), that also reported the destruction of A. suum eggs after 21 days of interaction in vitro, with P. chlamydosporia (VC4 and VC1) grown in 2%WA medium. However, these studies have been conducted only in laboratory conditions, the fungus was already grown.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Still, for chlamydospores production is important to stand out this structure viability for its use in biological control environment (Larsen 1999;Terrill et al 2004) The present study showed A. suum eggs destruction (type 3 effect) by P. chlamydosporia isolates (VC4 and VC1) after a long period of interaction. These results are in agreement with Ferreira et al (2011) and Araújo et al (2008), that also reported the destruction of A. suum eggs after 21 days of interaction in vitro, with P. chlamydosporia (VC4 and VC1) grown in 2%WA medium. However, these studies have been conducted only in laboratory conditions, the fungus was already grown.…”
Section: Discussionsupporting
confidence: 93%
“…In this study the fungus P. chlamydosporia passed through the swines gastrointestinal tract, germinated from their feces and destroyed the A. suum eggs at the end of 30 days of interaction. Still in comparisons to the work of Ferreira et al (2011) and Araújo et al (2008), the obtained destruction percentages for VC4 and VC1 were the following: (57.67% and 55.3%) and (19% and 20%), respectively, at the end of study. The results in present study were similar (Table 1), at little different conditions.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…chlamydosporia has also been applied to control animal parasitic nematodes (Ferreira et al 2011;Silva et al 2011) or other plantpathogenic fungi. Together with Pochonia rubescens and Lecanicillium lecanii, isolate 4624 was capable to reduce root colonisation and damage caused by the fungus Gaeumannomyces graminis var.…”
Section: Plant Protection and Nematode Managementmentioning
confidence: 99%
“…Pasture rotation is recommended for trying to reduce the risk of ascariosis among grazing animals. More recently, the usefulness of some soil fungi as Pochonia chlamydosporia against eggs of trematodes (Fasciola hepatica) and ascarids (Toxocara canis, Toxocara vitulorum, Ascaris suum) has been reported (Frassy et al, 2010;Carvalho et al, 2010;Ferreira et al, 2011).…”
Section: Introductionmentioning
confidence: 99%